Actividad insecticida y repelente de aceites esenciales de laurel y lemongraá sobre Bemisia tabaci - Ringuelet, J.A.=700 1 Urrutia, M.I.; Yordaz, R.M.; Henning, C.P.
(Es, En)
Ilus., 32 ref.
Keywords: BEMICIA TABACI; CYMBOPOGON CITRATUS; LAURUS NOBILIS; REPELENTES; MORTALIDAD; ESPAÑA